Mixed convection in a rotating eccentric annulus containing nanofluid using bi-orthogonal grid types: A finite volume simulation - Teimouri, Hamid; Sheikhzadeh, Ghanbar Ali; Afrand, Masoud; Fakhari, Mohammad Mahdi (Journal of molecular liquids, 2017)
In this paper, the steady state and laminar mixed convection of nanofluid in horizontal eccentric annulus with rotating inner cylinder has been investigated numerically. The inner and outer cylinders are considered at constant temperature Ti and To respectively, where Ti>To. The annular space is filled with Alumina-water nanofluid. The nonlinear governing equations and the associated boundary conditions in the polar coordinate are solved numerically using the finite volume method and SIMPLER algorithm. In order to perform the numerical simulations, a code has been written to model the problem using bipolar orthogonal co-ordinates as well as non-orthogonal co-ordinates grid types. It is worth mentioning that in non-orthogonal co-ordinates grid types the code is able to model the problem with or without the effects of non-orthogonality. Due to the inconsiderable non-orthogonality of the grid, difference between the results of three schemes is <3%. Considering the computational cost, the code developed for non-orthogonal co-ordinates grid types without effects of non-orthogonality has been used for this study. The effects of the eccentricity and the nanoparticle volume fraction on the heat transfer inside the annuli have been investigated. According to the results, the average Nusselt number increases by increasing the downward eccentricity of the inner cylinder. Furthermore, the maximum average Nusselt number occurs for an optimal nanoparticle volume fraction. •Simulation of mixed convection of nanofluid in horizontal eccentric annulus•Using orthogonal and non-orthogonal co-ordinates grid types to model the problem•Investigation of effects of eccentricity and volume fraction on heat transfer•Average Nusselt number increases by increasing the downward eccentricity•Maximum average Nusselt number occurs for an optimal nanoparticle volume fraction.